IJIRST –International Journal for Innovative Research in Science & Technology| Volume 3 | Issue 04 | September 2016 ISSN (online): 2349-6010
Fuzzy and Anti-Fuzzy Normal HX Subring of A HX Ring R. Muthuraj Department of Mathematics H. H. The Rajah’s College, Pudukkottai – 622001, Tamilnadu, India
N. Ramila Gandhi Department of Mathematics PSNA College of Engineering and Technology, Dindigul-624 622, Tamilnadu, India
Abstract In this paper, we define the concept of a fuzzy and anti-fuzzy normal HX subring of a HX ring also discuss some related properties of it. Keywords: HX Ring, Fuzzy HX Ring, Fuzzy Set, Fuzzy Normal HX Subring, Anti-Fuzzy Normal HX Subring _______________________________________________________________________________________________________ I.
INTRODUCTION
In 1965, Zadeh [15] introduced the concept of fuzzy subset of a set X as a function from X into the closed interval 0 and 1 and studied their properties. Fuzzy set theory is a useful tool to describe situations in which the data or imprecise or vague and it is applied to logic , set theory, group theory, ring theory, real analysis, measure theory etc. In 1967, Rosenfeld [13] defined the idea of fuzzy subgroups and gave some of its properties. In 1988, Professor Li Hong Xing [6] proposed the concept of HX ring and derived some of its properties, then Professor Zhong [1,2] gave the structures of HX ring on a class of ring. In this paper, we define the concept of fuzzy normal HX ring and anti-fuzzy normal HX ring of a HX ring by establishing the relation among them and discussed its properties. We also discuss some results based on homomorphism and anti-homomorphism of a fuzzy normal HX ring and anti-fuzzy normal HX ring of a HX ring. II. PRELIMINARIES In this section, we site the fundamental definitions that will be used in the sequel. Throughout this paper, R = (R, +, ·) is a Ring, e is the additive identity element of R and xy, we mean x.y. III. FUZZY NORMAL HX RING In this section we define the concept of fuzzy normal HX ring and discuss some related results. Definition Let R be a ring. Let μ be a fuzzy set defined on R. Let 2R –{} be a HX ring. A fuzzy HX subring of is called a fuzzy normal HX ring on or a fuzzy normal ring induced by μ if the following conditions are satisfied. For all A , B , (AB) = (BA), where (A) = max {μ(x) /for all xA R }. Example In Example C [10], is a fuzzy HX ring on . For all A , B , ( AB) = (BA). Hence, is a fuzzy normal HX ring on . Theorem If μ is a fuzzy normal subring of a ring R then the fuzzy subset is a fuzzy normal HX subring of a HX ring . Proof Let μ be a fuzzy normal subring of R. That is, μ(xy) = μ(yx), for all x,y R. By Theorem ‘D’ [10], is a fuzzy HX subring on . For all A, B , (AB) = max{μ(xy) / for all xy AB R } = max{μ(yx) / for all xy AB R }, = (BA) (AB) = (BA). Hence, is a fuzzy normal HX subring of a HX ring .
All rights reserved by www.ijirst.org
367
Fuzzy and Anti-Fuzzy Normal HX Subring of A HX Ring (IJIRST/ Volume 3 / Issue 04/ 057)
Theorem Let and be any two fuzzy sets defined on R. Let and be any two fuzzy normal HX subrings of a HX ring then the intersection of two fuzzy normal HX subrings, is also a fuzzy normal HX subring of a HX ring . Proof Let and be any two fuzzy sets defined on R. Let and be any two fuzzy normal HX subrings of a HX ring . By Theorem ‘H’ [10], is a fuzzy HX subring of a HX ring . Let A, B . ( )(AB) = min{ (AB), (AB)} = min{ (BA), (BA)}, = ( )(BA). ( )(AB) = ( )(BA). Hence, is a fuzzy normal HX subring of a HX ring . Remark
The intersection of family of fuzzy normal HX subrings of a HX ring is also fuzzy normal HX subring of . Let R be a ring. Let μ and are fuzzy sets of R and μ is also a fuzzy set of R then φ is a fuzzy normal HX subring of induced by μ of R. Theorem
If , , φ are fuzzy normal HX subrings of a HX ring induced by the fuzzy sets μ, , μ of R then φ = . Proof By Theorem ‘J’ [10], it is clear. Theorem Let μ and be fuzzy sets of R. Let 2R – {} be a HX ring. If and are any two fuzzy normal HX subrings of then is a fuzzy normal HX subring of . Proof Let μ and be fuzzy sets of R. Let and be any two fuzzy normal HX subrings of . By Theorem ‘M’[ 10] , is a fuzzy HX subring of . Let A, B . ( ) (AB) = max{ (AB), (AB)} = max{ (BA), (BA)} = ( )(BA). ( )(AB) = ( )(BA). Hence, is a fuzzy normal HX subring of . Remark
Union of family of fuzzy normal HX subrings of a HX ring is also fuzzy normal HX subring of . Let R be a ring. Let μ and are fuzzy sets of R then φ is a fuzzy normal HX subring of induced by the fuzzy set μ of R. Theorem
Let R be a ring. Let μ and be fuzzy sets of R. If , , φ are fuzzy normal HX subrings of a HX ring induced by μ, , μ of R then φ = . Proof By Theorem ‘O’ [10], it is clear. Theorem Let and be fuzzy normal HX subrings of HX rings 1 and 2 respectively then × is also a fuzzy normal HX subring of a HX ring 1 × 2. Proof Let μ and be fuzzy sets of R. Let and be any two fuzzy normal HX subrings of 1 and 2 respectively.
All rights reserved by www.ijirst.org
368
Fuzzy and Anti-Fuzzy Normal HX Subring of A HX Ring (IJIRST/ Volume 3 / Issue 04/ 057)
By Theorem ‘Q’ [10], × is a fuzzy HX subring of 1 × 2. Let (A, B), (C, D) 1 × 2. ( × ) ((A, B)·(C ,D)) = ( × ) (AC, BD) = min { (AC), (BD)} = min{ (CA), (DB)} = ( × ) (CA , DB) = ( × ) ((C, D) · (A , B)) ( × ) ((A, B) · (C,D)) = ( × ) ((C, D) · (A , B)). Hence, × is a fuzzy normal HX subring of a HX ring 1 × 2. Theorem Let and be fuzzy subsets of the HX rings 1 and 2 respectively, such that (A ) ≤ ( Q1 ) for all A 1 , Q1 being the identity element of 2 . If ( × ) is a fuzzy normal HX subring of 1 × 2 then is a fuzzy normal HX subring of 1. Proof Let × be a fuzzy normal HX subring of 1 × 2. By Theorem ‘S’[10], is a fuzzy HX subring of 1. Let A, B 1. Given, (A ) ≤ ( Q1 ) for all A 1. (AB) = min { (AB), (Q1Q1)} = ( × )((A, Q1 ) · (B , Q1)) = ( × )( (B , Q1) · (A, Q1 )) = min { (BA), (Q1Q1)} = (BA). (AB) = (BA). Hence, is a fuzzy normal HX subring of 1. Theorem Let and be fuzzy subsets of the HX rings 1 and 2 respectively , such that (A ) ≤ (Q ) for all A 2 , Q being the identity element of 1. If × is a fuzzy normal HX sub ring of 1 × 2 then is a fuzzy normal HX subring of 2. Proof Let × be a fuzzy normal HX subring of 1 × 2. By Theorem ‘T’ [10], is a fuzzy HX subring of 2. Let A, B 2. Given, (A) ≤ ( Q ) for all A 2. (AB) = min {(QQ), (AB)} = ( × )((Q , A) · (Q , B)) = ( × )((Q , B) · (Q , A)) = min {(QQ), (BA)} = (BA) (AB) = (BA) Hence, is a fuzzy normal HX subring of 2. IV. HOMOMORPHISM AND ANTI-HOMOMORPHISM OF A FUZZY NORMAL HX SUBRING OF A HX RING In this section, we introduce the concept of an image, pre-image of fuzzy subset of a HX ring and discuss the properties of homomorphic and anti homomorphic images and pre images of fuzzy normal HX subring of a HX ring . Theorem Let 1 and 2 be any two HX rings on the rings R 1 and R2 respectively. Let f : 1 2 be a homomorphism onto HX rings. Let λ be a fuzzy normal HX subring of 1 then f ( λ ) is a fuzzy normal HX subring of 2 , if λ has a supremum property and λ is f-invariant. Proof Let be a fuzzy subset of R1 and λ is a fuzzy normal HX subring of 1. By Theorem 3.4[12], f ( λ ) is a fuzzy HX subring of 2.
All rights reserved by www.ijirst.org
369
Fuzzy and Anti-Fuzzy Normal HX Subring of A HX Ring (IJIRST/ Volume 3 / Issue 04/ 057)
There exist X,Y 1 such that f(X), f(Y) 2, (f (λ)) (f(X) f(Y)) = (f (λ)) (f(XY)) , = λ (XY) = λ (YX) = (f (λ)) (f(YX)) = (f (λ)) (f(Y)f(X)) (f (λ )) (f(X)f(Y)) = (f (λ)) (f(Y)f(X)). Hence, f (λ ) is a fuzzy normal HX subring of 2. Theorem Let 1 and 2 be any two HX rings on R1 and R2 respectively. Let f: 1 2 be a homomorphism on HX rings. Let be a fuzzy normal HX subring of 2 then f –1 () is a fuzzy normal HX subring of 1. Proof Let be a fuzzy subset of R2 and be a fuzzy normal HX subring of 2 . By Theorem 3.5 [12], f –1 () is a fuzzy HX subring of 1. For any X,Y 1, f(X) , f(Y) 2, (f –1()) (XY) = (f(XY)) = (f(X) f(Y)) = (f(Y) f(X)) = (f(YX)) = (f –1()) (YX) –1 (f ( )) (XY) = (f –1()) (YX) –1 Hence, f ( ) is a fuzzy normal HX subring of 1. Theorem Let 1 and 2 be any two HX rings on R1 and R2 respectively. Let f: 1 2 be an anti homomorphism onto HX rings. Let λ be a fuzzy normal HX subring of 1, then f(λ) is a fuzzy normal HX subring of 2 , if λ has a supremum property and λ is f-invariant. Proof Let be a fuzzy subset of R1 and λ is a fuzzy normal HX subring of 1. By Theorem 3.6[12], f (λ ) is a fuzzy HX subring of 2. There exist X, Y 1 such that f(X), f(Y) 2, (f (λ)) (f(X) f(Y)) = (f (λ)) (f(YX)) , = λ (YX) = λ (XY) = (f (λ)) (f(XY)) = (f (λ)) (f(Y)f(X)) (f (λ )) (f(X)f(Y)) = (f (λ)) (f(Y)f(X)). Hence, f (λ ) is a fuzzy normal HX subring of 2. Theorem Let 1 and 2 be any two HX rings on R1 and R2 respectively. Let f: 1 2 be an anti homomorphism on HX rings. Let be a fuzzy normal HX subring of 2 then f –1() is a fuzzy normal HX subring of 1. Proof Let be a fuzzy subset of R2 and be a fuzzy normal HX subring of 2 . By Theorem 3.7 [12], f –1 () is a fuzzy HX subring of 1. For any X,Y 1, f(X) , f(Y) 2, (f –1()) (XY) = (f(XY)) = (f(Y) f(X)) = (f(X) f(Y)) = (f(YX)) = (f –1()) (YX) –1 (f ( )) (XY) = (f –1()) (YX) –1 Hence, f ( ) is a fuzzy normal HX subring of 1.
All rights reserved by www.ijirst.org
370
Fuzzy and Anti-Fuzzy Normal HX Subring of A HX Ring (IJIRST/ Volume 3 / Issue 04/ 057)
V. ANTI-FUZZY NORMAL HX RING In this section we define the concept of anti-fuzzy normal HX ring and discuss some related results. Definition Let R be a ring. Let μ be a fuzzy set defined on R. Let 2R – {} be a HX ring. A fuzzy HX subring of is called an antifuzzy normal HX ring on or an anti-fuzzy ring induced by μ if the following conditions are satisfied. For all A , B , (AB) = (BA), where (A) = min { μ(x)/for all xA R }. Theorem If μ is an anti-fuzzy normal subring of a ring R then the fuzzy subset is an anti-fuzzy normal HX subring of a HX ring . Proof Let μ be an anti-fuzzy normal subring of R. That is, μ(xy) = μ(yx), for all x,y R. By Theorem 3.6 [11] , is an anti-fuzzy normal HX subring of a HX ring . For all A, B , (AB) = min{μ(xy) / for all xy AB R } = min{μ(yx) / for all xy AB R } = (BA) (AB) = (BA). Hence, is an anti-fuzzy normal HX subring of a HX ring . Theorem Let μ and be any two fuzzy sets of R. Let 2R – {} be a HX ring. Let and be any two fuzzy normal HX subrings of a HX ring then the intersection of two anti-fuzzy normal HX subrings, is also an anti-fuzzy normal HX subring of a HX ring . Proof It is clear. Remark
The intersection of family of anti-fuzzy normal HX subrings of a HX ring is also an anti-fuzzy HX subring of . Let R be a ring. Let μ and are fuzzy sets of R and μ is also a fuzzy subset of R then φ is an anti-fuzzy normal HX subring of induced by μ of R. Theorem
Let R be a ring. Let μ and are fuzzy sets of R. If , , φ are anti-fuzzy normal HX subrings of a HX ring induced by μ , , μ of R then φ = . Proof It is clear. Theorem Let μ and are any two fuzzy sets of R. Let 2R – {} be a HX ring. If and be any two anti-fuzzy normal HX subrings of then is also an anti-fuzzy normal HX subring of . Proof It is clear. Remark
Union of family of anti-fuzzy normal HX subrings of a HX ring is also an anti-fuzzy normal HX subring of . Let R be a ring. Let μ and be fuzzy sets of R then φ is an anti-fuzzy normal HX subring of induced by μ of R. Theorem
Let R be a ring. Let μ and be fuzzy sets of R. If , , φ are anti-fuzzy normal HX subrings of a HX ring induced by μ , , μ of R then φ = . Proof It is clear.
All rights reserved by www.ijirst.org
371
Fuzzy and Anti-Fuzzy Normal HX Subring of A HX Ring (IJIRST/ Volume 3 / Issue 04/ 057)
Theorem Let and be anti-fuzzy normal HX subrings of HX rings 1 and 2 respectively then the cartesian anti-product of and denoted as × is also an anti-fuzzy normal HX subring of 1 × 2. Proof Let μ and be fuzzy sets of R. Let and be anti-fuzzy normal HX subrings of HX rings 1 and 2 respectively. By Theorem 4.2[11], × is an anti-fuzzy HX subring of 1 × 2. Let (A, B), (C, D) 1 × 2. ( × ) ((A, B)·(C ,D)) = (× ) (AC, BD) = max{ (AC), (BD)} = max{ (CA), (DB)} = ( × ) (CA, DB) = ( × ) ((C, D) · (A , B)) ( × ) ((A, B)·(C ,D)) = ( × ) ((C, D) · (A , B)). Hence, × is also an anti-fuzzy normal HX subring of a HX ring . Theorem Let and be fuzzy subsets of the HX rings 1 and 2 respectively, such that (A ) ( Q1) for all A 1, Q1 being the identity element of 2 .If ( × ) is an anti-fuzzy normal HX subring of 1 × 2 then is an anti-fuzzy normal HX subring of 1. Proof Let ( × ) is an anti-fuzzy normal HX subring of 1 × 2. By Theorem 4.3[11], is an anti-fuzzy HX subring of 1. Given, (A) (Q1) for all A 1. (AB) = max { (AB), (Q1Q1)} = ( × ) ((A, Q1 ) · (B , Q1)) = ( × ) ( (B , Q1) · (A, Q1 )) = max { (BA), (Q1Q1)} = (BA) (AB) = (BA) Hence, is an anti-fuzzy normal HX subring of 1. Theorem Let and be fuzzy subsets of the HX rings 1 and 2 respectively , such that (A ) (Q ) for all A 2 , Q being the identity element of 1. If × is an anti-fuzzy normal HX sub ring of 1 × 2 then is an anti-fuzzy normal HX subring of 2. Proof Let × be an anti-fuzzy normal HX subring of 1 × 2. By Theorem 4.4[11], is an anti-fuzzy HX subring of 2. Let A, B 2. Given (A) (Q) for all A 2 (AB) = max {(QQ), (AB)} = (×) ((Q, A) · (Q, B)) = (×) ((Q, B) · (Q, A)) = max {(QQ), (BA)} (AB) = (BA)}. Hence, is an anti-fuzzy normal HX subring of 2. Theorem Let be a fuzzy set defined on R. Let λμ be a fuzzy normal HX subring of if and only if (λμ)c is an anti-fuzzy normal HX subring of . Proof It is clear.
All rights reserved by www.ijirst.org
372
Fuzzy and Anti-Fuzzy Normal HX Subring of A HX Ring (IJIRST/ Volume 3 / Issue 04/ 057)
VI. HOMOMORPHISM AND ANTI-HOMOMORPHISM OF AN ANTI-FUZZY NORMAL HX SUBRING OF A HX RING In this section, we introduce the concept of an anti-image, anti-pre-image of an anti-fuzzy normal HX subring of a HX ring and discussed its properties under homomorphism and anti-homomorphism. Theorem Let 1 and 2 be any two HX rings on the rings R1 and R2 respectively. Let f: 1 2 be a homomorphism onto HX rings. Let λ be an anti-fuzzy normal HX subring of 1 then f ( λ ) is an anti-fuzzy normal HX subring of 2, if λ has an infimum property and λ is f-invariant. Proof Let be a fuzzy subset of R1 and λ is an anti-fuzzy HX subring of 1. There exist X, Y 1 such that f(X) , f(Y) 2, (f (λ)) (f(X) – f(Y)) = (f (λ)) (f(X–Y)), = λ (X–Y) max {λ (X), λ (Y)} = max {(f (λ)) (f(X)), (f (λ)) (f(Y))} (f (λ)) (f(X) – f(Y)) max {(f (λ)) (f(X)), (f (λ)) (f(Y))}. ((f (λ)) (f(X) f(Y)) = (f (λ)) (f(XY)) , = λ (XY) max {λ (X), λ (Y)} = max {(f (λ)) (f(X)), (f (λ)) (f(Y))} (f (λ)) (f(X)f(Y)) max {(f (λ)) (f(X) , (f (λ)) (f(Y))}. Hence, f (λ) is an anti-fuzzy HX subring of 2. Also (f (λ)) (f(X) f(Y)) = (f (λ)) (f(XY)) , = λ (XY) = λ (YX) = (f (λ)) (f(YX)) (f (λ)) (f(X)f(Y)) = (f (λ)) (f(Y)f(X)). Hence, f (λ) is an anti-fuzzy normal HX subring of 2. Theorem Let 1 and 2 be any two HX rings on R1 and R2 respectively. Let f: 1 2 be a homomorphism on HX rings. Let be an anti-fuzzy normal HX subring of 2 then f –1 () is an anti-fuzzy normal HX subring of 1. Proof Let be a fuzzy subset of R2 and be an anti-fuzzy HX subring of 2 . For any X,Y 1, f(X) , f(Y) 2, (f –1()) (X–Y) = (f(X–Y)) = (f(X) – f(Y)), max { (f(X)) , (f(Y))} = max {(f –1()) (X) , (f –1()) (Y)} –1 (f ()) (X–Y) max{( f –1()) (X) , (f –1()) (Y)}. (f –1()) (XY) = (f(XY)) = (f(X) f(Y)) max { (f(X)) , (f(Y))} = max {(f –1()) (X), (f –1()) (Y)} (f –1()) (XY) max{(f –1()) (X) , (f –1()) (Y)}. Hence, f –1() is an anti-fuzzy HX subring of 1. Also, (f –1()) (XY) = (f(XY)) = (f(X) f(Y)) = (f(Y) f(X)) = (f(YX)) = f –1()) (YX) (f –1()) (XY) = f –1()) (YX). –1 Hence, f () is an anti-fuzzy normal HX subring of 1.
All rights reserved by www.ijirst.org
373
Fuzzy and Anti-Fuzzy Normal HX Subring of A HX Ring (IJIRST/ Volume 3 / Issue 04/ 057)
Theorem Let 1 and 2 be any two HX rings on the rings R1 and R2 respectively. Let f: 1 2 be an anti-homomorphism onto HX rings. Let λ be an anti-fuzzy normal HX subring of 1 then f ( λ ) is an anti-fuzzy normal HX subring of 2 , if λ has an infimum property and λ is f-invariant. Proof Let be a fuzzy subset of R1 and λ is an anti-fuzzy HX subring of 1, then There exist X, Y 1 such that f(X), f (Y) 2 (f (λ)) (f(X) – f(Y)) = (f (λ)) (f(Y–X)) , = λ (Y–X) max {λ (Y), λ (X)} = max {(f (λ)) (f(Y)), (f (λ)) (f(X))} (f (λ)) (f(X) – f(Y)) max {(f (λ)) (f(X)), (f (λ)) (f(Y))}. (f (λ)) (f(X) f(Y)) = (f (λ)) (f(YX)), = λ (YX) max {λ (Y), λ (X)} = max {(f (λ)) (f(Y)), (f (λ)) (f(X))} (f (λ)) (f(X)f(Y)) max {(f (λ)) (f(X)) , (f (λ)) (f(Y))}. Hence, f (λ) is an anti-fuzzy HX subring of 2. Also (f (λ)) (f(X) f(Y)) = (f (λ)) (f(YX)) , = λ (YX) = λ (XY) = (f (λ)) (f(XY)) (f (λ)) (f(X)f(Y)) = (f (λ)) (f(Y)f(X)). Hence, f (λ) is an anti-fuzzy normal HX subring of 2. Theorem Let 1 and 2 be any two HX rings on R1 and R2 respectively. Let f: 1 2 be an anti-homomorphism on HX rings. Let be an anti-fuzzy normal HX subring of 2 then f–1 () is an anti-fuzzy normal HX subring of 1. Proof Let be a fuzzy subset of R2 and be an anti-fuzzy HX subring of 2 . For any X,Y 1, then f (X ) , f ( Y ) 2 (f –1()) (X–Y) = (f(Y–X)) = (f(Y) – f(X)), max { (f(Y)), (f(X))} max {(f –1()) (Y), (f –1()) (X)} –1 (f ()) (X–Y) max{( f –1()) (X), (f –1()) (Y)}. (f –1()) (XY) = (f(YX)) = (f(Y) f(X)) max { (f(Y)), (f(X))} min {(f –1()) (Y), (f –1()) (X)} –1 (f ()) (XY) max{( f –1()) (Y), (f –1() )(X)}. –1 Therefore, f () is an anti-fuzzy HX subring of 1. Also, (f –1()) (XY) = (f(XY)) = (f(Y) f(X)) = (f(X) f(Y)) = (f(YX)) = f –1()) (YX) (f –1()) (XY) = f –1()) (YX). –1 Hence, f () is an anti-fuzzy normal HX subring of 1. REFERENCES [1] [2] [3]
Bing-xueYao and Yubin-Zhong, The construction of power ring, Fuzzy information and Engineering (ICFIE),ASC 40,pp.181-187,2007. Bing-xueYao and Yubin-Zhong, Upgrade of algebraic structure of ring, Fuzzy information and Engineering (2009)2:219-228. Dheena.P and Mohanraaj.G, T- fuzzy ideals in rings ,International Journal of computational cognition, volume 9, No.2, 98-101, June 2011 .
All rights reserved by www.ijirst.org
374
Fuzzy and Anti-Fuzzy Normal HX Subring of A HX Ring (IJIRST/ Volume 3 / Issue 04/ 057) [4] [5] [6] [7] [8] [9] [10] [11] [12] [13] [14] [15]
Li Hong Xing, HX group, BUSEFAL,33(4), 31-37,October 1987. Liu. W.J., Fuzzy invariant subgroups and fuzzy ideals, Fuzzy sets and systems,8:133-139. Li Hong Xing, HX ring, BUSEFAL ,34(1) 3-8,January 1988. Mashinchi.M and Zahedi.M.M, On fuzzy ideals of a ring,J.Sci.I.R.Iran,1(3),208- 210(1990) Mukherjee.T.K & Sen.M.K., On fuzzy ideals in rings, Fuzzy sets and systems,21, 99- 104,1987. Muthuraj.R, Ramila Gandhi.N, Homomorphism and anti-homomorphism of fuzzy HX ideals of a HX ring, Discovery, Volume 21, Number 65, July 1, 2014, pp 20-24. Muthuraj.R, Ramila Gandhi.N., Fuzzy HX Subring of a HX Ring , International Journal for Research in Applied Science & Engineering Technology ( IJRASET), Volume 4 Issue VI, June 2016, pp.532-540. Muthuraj.R, Ramila Gandhi.N., Anti-fuzzy HX ring and its level sub HX ring, International Journal of Mathematics Trends and Technology (IJMTT), Volume 31 Number 2,March 2016,pp. 95-100. Muthuraj.R, Ramila Gandhi.N., Homomorphism on fuzzy HX Ring , International Journal of Advanced Research in Engineering Technology & Sciences ( IJARETS), Volume 3, Issue 7, July 2016, pp.45-54. Rosenfeld. A., Fuzzy groups,J.Math.Anal.,35(1971),512-517. Wang Qing –hua ,Fuzzy rings and fuzzy subrings ,pp.1-6. Zadeh.L.A., Fuzzy sets, Information and control,8,338-353.
All rights reserved by www.ijirst.org
375